THE IMPLEMENTATION OF RESTORATIVE JUSTICE SYSTEM TO RESOLVE DOMESTIC VIOLENCE ACTS - Hardianto, Yoyok; Khoidin, M.; Prawesthi, Wahyu; Utami, Rahayu Sri (YURIS: Journal of Court and Justice, 2023)
Domestic violence is often referred to as a hidden crime because both perpetrators and victims attempt to hide their offence from public view. According to Article 28 of the 1945 Constitution, which regulates human rights, all forms of violence, especially domestic violence, are violations of human rights and crimes against human dignity. Restorative justice system is one of the approaches used to resolve case of domestic violence. The concept of a restorative justice system is used to resolve violations of the law that occur based on victims and perpetrators’ interests. The objectives of this research is to find out the implementation of restorative justice in managing domestic violence issues in society; and to analyse the restorative justice mechanism in domestic violence cases based on the Indonesian legal system. The approach method used in this research is a normative juridical approach based on laws and regulations related to legal issues. In addition, it is also used conceptual approach based on developed perspective and doctrines in legal sciences. The settlement of domestic violence cases using penal mediation method with a restorative justice approach was succesfully resolved the criminal cases occurred in community.